Influence of physical recreation of students with disabilities on indicators of their psychophysiological status - Vedernikova E.V. ,; Morozova M.A. ,; Kovyazina G.V. ,; Makarov A.V. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to identify indicators of the psychophysical status of students with disabilities, which must be taken into account when designing and organizing physical recreation for students with health limitations and disabilities. Methods and structure of the study. The scientific work was carried out at Vyatka State University using the psychomotor test module UPFT-1/30 “Psychophysiologist”; 14 students aged 17-22 years old with disabilities of different nosological groups and 14 students of the same age who did not have pathology took part in it. Based on the tests performed (tapping test, simple visual-motor reaction and reaction to a moving object), the functional state of the nervous system of the study population was assessed, and the level of reactive and personal anxiety was determined. Results and conclusions. Indicators of the psychophysiological status of students with disabilities differ significantly from those of students without pathology in the leading hemisphere of the brain and the leading analyzer, in the level of activation of the nervous system and the level of personal anxiety. Taking into account the data we received, we developed a method of physical recreation with elements of rehabilitation for students with disabilities, and also formulated recommendations for its organization.